Health Education Approach In Congenital Hypothyroidism Screening: Sytematic Review - Ropitasari Ropitasari; Fanny Kartika Fajriyani; Nahdiyah Karimah; Fatiya 'Izzatuna Tsiqqoh (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Congenital hypothyroidism (CH) is a preventable cause of intellectual disability in newborns if detected early through neonatal screening. Maternal knowledge and health promotion interventions are critical to ensure timely screening and treatment. This study systematically reviews evidence on maternal education, knowledge, attitude, and promotional strategies for CH screening. Subjects and Method: This study uses a systematic review conducted by searching for articles from several databases, namely ScienceDirect, MDPI, PubMed, Springer Nature Link, and Taylor & Francis Group and Google Scholar with a search range from 2019-2025. The keywords used to search for articles were